Hubungan Antara Pemberian Informasi Hak dan Tanggung Jawab Pasien Dengan Tingkat Kepuasan Pasien di Ruang Rawat Inap RSUD Ratu Zalecha Martapura - Andin Nur Azwa; Rohni Taufikasari; M. Fahrin Azhari; Yustan Azidin (Malahayati Nursing Journal, 2026)
ABSTRACT Patient satisfaction is an important indicator in assessing the quality of hospital services. One factor that is presumed to influence patient satisfaction is the provision of clear information regarding patients’ rights and responsibilities during inpatient care. A lack of patient understanding of this information may lead to discomfort and a decline in perceived service quality. This study aimed to determine the relationship between the provision of information on patients’ rights and responsibilities and patient satisfaction in the inpatient wards of RSUD Ratu Zalecha Martapura. This study employed a quantitative approach with an observational analytic design using a cross-sectional method. The population consisted of adult patients in class 1 and class 2 who had been hospitalized for at least 2×24 hours in five inpatient wards at RSUD Ratu Zalecha Martapura. A total of 76 respondents were selected using purposive sampling. Data were collected using questionnaires and analyzed using the Spearman’s rank correlation test. The results showed that the majority of respondents perceived the provision of information on patients’ rights and responsibilities as inadequate (63.2%). Patient satisfaction levels were evenly distributed between the satisfied and moderately satisfied categories, each accounting for 50.0% of respondents. Bivariate analysis revealed a p-value of 0.640 (0.05), indicating that there was no significant relationship between the provision of information on patients’ rights and responsibilities and patient satisfaction. In conclusion, the provision of information regarding patients’ rights and responsibilities was not significantly associated with patient satisfaction in the inpatient wards of RSUD Ratu Zalecha Martapura. Nevertheless, improving the quality and consistency of information delivery remains essential as part of efforts to enhance overall hospital service quality. Keywords: Provision of Information, Patient Rights and Responsibilities, Patient Satisfaction.  ABSTRAK Kepuasan pasien merupakan indikator penting dalam menilai mutu pelayanan rumah sakit, salah satunya dipengaruhi oleh pemberian informasi yang jelas mengenai hak dan tanggung jawab pasien selama menjalani perawatan rawat inap. Kurangnya pemahaman pasien terhadap informasi tersebut dapat menimbulkan ketidaknyamanan dan menurunkan kualitas pelayanan yang dirasakan. Penelitian ini bertujuan untuk mengetahui hubungan antara pemberian informasi hak dan tanggung jawab pasien dengan tingkat kepuasan pasien di ruang rawat inap RSUD Ratu Zalecha Martapura. Penelitian ini menggunakan pendekatan kuantitatif dengan desain analitik observasional melalui metode cross-sectional. Populasi penelitian adalah pasien dewasa kelas 1 dan kelas 2 yang menjalani rawat inap minimal 2×24 jam di lima ruang rawat inap RSUD Ratu Zalecha Martapura, dengan jumlah sampel sebanyak 76 responden yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan uji korelasi Spearman. Hasil penelitian menunjukkan bahwa sebagian besar responden menilai pemberian informasi hak dan tanggung jawab pasien berada pada kategori kurang (63,2%), sementara tingkat kepuasan pasien terbagi secara merata antara kategori puas dan cukup (masing-masing 50,0%). Hasil analisis bivariat menunjukkan nilai p = 0,640 (0,05), yang menandakan tidak terdapat hubungan yang bermakna antara pemberian informasi hak dan tanggung jawab pasien dengan tingkat kepuasan pasien. Dengan demikian, dapat disimpulkan bahwa pemberian informasi hak dan tanggung jawab pasien belum berhubungan secara signifikan dengan tingkat kepuasan pasien, meskipun peningkatan kualitas dan konsistensi pemberian informasi tetap diperlukan sebagai bagian dari upaya peningkatan mutu pelayanan rumah sakit. Kata Kunci: Pemberian Informasi, Hak dan Tanggung Jawab Pasien, Kepuasan Pasien.